Peningkatan Ekonomi Masyarakat di Tengah Pandemi Covid 19 melalui Home Industri dengan Memanfaatkan Kain Perca di Desa Kranji Paciran Lamongan - Muslih Muslih; Abd Hadi; Ahmad Afan Zaini (KERIS : Journal of Community Engagement, 2021)
The maximization of an asset owned by a village, is a thing that is still rare. This mentoring is therefore done in an attempt to make the existing potential in an area more maximal, from objects considered already unfavourable to more economically valued objects. So that potential could make the surrounding communities more established and economically prosperous. This asset-consistency mentoring is done with the ABCD (Asset Base Community Development) approach with several stages among others: Preparing; Discovery; Dream; Define; Design; and Destiny. As for the measures undertaken in the effort to improve the community economy of the Kranji Paciran Lamongan through industrial Home with Perca fabric assets, namely: socialization and coordination activities; interview activities; form discussion forums; production mentoring; marketing/marketing mentoring; and mentoring of financing. The product results of the Perca fabric material were very manifold. For example: marker boxes; pencil boxes; doormats; miscellaneous ornaments and learning media. With this mentoring program, it is expected that the public will always be moved to further innovate leveraging locally owned opportunities and assets so that there is an economic discord for the community for the sake of a more prosperous future.